Parasocial Relationship Activities in BLACKPINK’s Fan Culture in social media Weverse - Pratama, Akhdan Naufal; Annisa, Firly (Universitas Muhammadiyah Yogyakarta, 2025)
Fan culture is a culture in which fans actively engage in efforts to get closer to the figures they idolize. Fans are always looking for new news about their idols. This also applies to the BLACKPINK fandom. BLACKPINK is a South Korean idol group that debuted in 2016 under YG Entertainment. BLACKPINK is known for being very close to its fans through various events and services provided, one of which is the Weverse membership. With this service, fans can access exclusive content directly from BLACKPINK members through the Weverse app, and fans can respond directly. The presence of this service facilitates the parasocial relationship that occurs on social media between fans and BLACKPINK. A parasocial relationship is a relationship in which fans feel they have a close connection with their idols. This study aims to determine the parasocial relationship activities of BLACKPINK on the Weverse social media platform to describe the parasocial relationship activities within the BLACKPINK fan culture on the Weverse social media platform. The method used in this study is phenomenology with a descriptive qualitative approach. The data collection techniques used in this study were interviews and documentation. The results of this study indicate that the existence of BLACKPINK's Weverse membership account is able to strengthen the parasocial relationship activities that occur on Weverse social media between fans and BLACKPINK, where BLACKPINK members send messages containing information about their daily activities using language as if they were communicating with someone they know well.